Case Study : IADZ Enterprise / Nurul Atikah Muhamad Daud - Muhamad Daud, Nurul Atikah (2020)
IADZ Enterprise has been chosen to be SME company that will be analyzed and solving any possible problem. IADZ Enterprise is a company that involve in activities of manufacturing and distribution of food, the process of the company heavily relied on the smooth operation process. Since the recent circumstances that occur in Malaysia, there is a restriction to done any face to face interview. Therefore, research on the company relied heavily on the videos of production, interviews, articles that involve with the company. Through the research that has been done online, student should be able to tackle any strength, weakness and possible problem that can be solved by using the recommended technology.